Substitusi Pakan Yang Berbeda Pada Pemeliharaan Induk Terhadap Pemijahan Lobster Air Tawar (Cherax quadricarinatus) - Farid Mudlofar; Sri Warastuti; Ridwan Salim; M. Taufik; Agus Setiawan; Hylda Khairah Putri (Fakultas Kelautan dan Perikanan Universitas Udayana, 2023)
Freshwater lobster (LAT) has been widely cultivated as a commodity for ornamental shrimp and consumption. In order to maintain the stock of seeds, it is necessary to have a hatchery. One of the problems that arose in hatchery activities was gonad maturation, especially feed, because sufficient nutrients can accelerate the maturity of the broodstock gonad. Currently, the main feed for broodstock is in the form of commercial pellets, which are still universal for various types of shrimp, and pellets are not yet available specifically to stimulate the gonad maturation of LAT broodstock. The proposed solution is to determine the type of substitution for pellet feed with similar effectiveness. The aimed of this study was to obtain a type of substitute feed that can replace pellets with the same or more effectiveness in the rearing process of freshwater crayfish so that the broodstock can be used to accelerate gonadal maturity and the spawning process. This study used a completely randomized design (CRD) with four treatments and three replications: (A) Acetes indicus, (B) Pomacea canaliculata, (C) Tubifex sp., and (D) Pellet Feed (control treatment). The results of this study after the Anova analysis concluded that all treatments had a significant effect on the percentage of the number of brooders laying eggs in the first to the third week. After further Tukey’s test was carried out, it was found that treatment C significantly gave the same effect as treatment D as the control treatment, so it is recommended that Tubifex sp. as a substitute for pelleted feed with the application of plant-based feeds.